Do Poor Paddy Farmers Benefit from Increasing Rice Prices? - Yogi Makbul; Nandan Limakrisna; Sudrajati Ratnaningtyas; Aryo Cokrowitianto (International Journal of Supply Chain Management, 2021)
A policy of high rice prices can increase paddy farm incomes but also cause a rise in rice expenditures for farm households. Such a policy is needed to stimulate production but can harm rice consumers, especially poor families. We surveyed 284 paddy farmers in Gantar Sub-District, Indramayu Regency, Indonesia to analyze the impact of increasing rice prices on farmers’ net incomes, including poor paddy farmers. We found that a price increase benefits farmer if the price transmission elasticity is more than 0.2 for non-poor paddy farmers or 0.6 for poor paddy farmers. A high rice price policy can benefit paddy farmers if there is good price transmission in the market. Good transmission requires a strong rice market efficiency channel.